CoTiO3/Ag3VO4 composite: A study on the role of CoTiO3 and the active species in the photocatalytic degradation of methylene blue - Kanlayawat Wangkawong (2018)
© 2015 Elsevier Inc. The role of CoTiO3 and the possible active species in the methylene blue (MB) degradation over the visible-light-driven CoTiO3/Ag3VO4 catalyst have firstly been investigated in this work. CoTiO3 is found to play important roles in enhancing the visible light-harvesting ability of the composite and increasing electron-hole separation efficiency due to the hybrid effect between Ag3VO4 and CoTiO3. The indirect probe experiments reveal that CoTiO3/Ag3VO4 heterostructure provides large amount of active species, therefore a high photocatalytic activity could be obtained. The results clearly suggest that the photocatalytic MB degradation over this hybrid catalyst is mainly governed by direct hole oxidation.